Off‐axis multilayer zone plate with 16 nm × 28 nm focus for high‐resolution X‐ray beam induced current imaging. (22nd July 2021) - Soltau, Jakob; Chayanun, Lert; Lyubomirskiy, Mikhail; Wallentin, Jesper; Osterhoff, Markus
Abstract : In an off‐axis geometry, a circular multilayer zone disc is used to locally generate X‐ray beam induced currents inside a single InP nanowire. This allows to spatially probe local electric fields at practical working distances and very low background signal. Abstract : Using multilayer zone plates (MZPs) as two‐dimensional optics, focal spot sizes of less than 10 nm can be achieved, as we show here with a focus of 8.4 nm × 9.6 nm, but the need for order‐sorting apertures prohibits practical working distances. To overcome this issue, here an off‐axis illumination of a circular MZP is introduced to trade off between working distance and focal spot size. By this, the working distance between order‐sorting aperture and sample can be more than doubled. Exploiting a 2D focus of 16 nm × 28 nm, real‐space 2D mapping of local electric fields and charge carrier recombination using X‐ray beam induced current in a single InP nanowire is demonstrated. Simulations show that a dedicated off‐axis MZP can reach sub‐10 nm focusing combined with reasonable working distances and low background, which could be used for in operando imaging of composition, carrier collection and strain in nanostructured devices.